Effect of pre-treatment with a tannin-based coagulant and flocculant on a biofilm bacterial community and the nitrification process in a municipal wastewater biofilm treatment unit. Issue 2 (April 2020) - Hameed, Yasir Talib; Idris, Azni; Hussain, Siti Aslina; Abdullah, Norhafizah; Che Man, Hasfalina
Highlights: Significant improvement in the nitrification process when Tanfloc was used. Nitrosomonas percentage jumped from 0.073 to 3.33 % when Tanfloc was used. Nitrospira percentage jumped from 0.19 to 7.8 % when Tanfloc was used. Abstract: Tanfloc, a natural tannin-based coagulant and flocculant, was used in this study as a pre-treatment agent for a biofilm unit that was used to treat municipal wastewater. The point of interest in this study was the effect of the extended use of Tanfloc (around 2 months) on the biofilm bacterial community. Two identical bench-scale aeration tanks were run in parallel, one of them treating settled wastewater, and the other pre-treated (flocculated/settled) wastewater using Tanfloc. The results showing the effect of Tanfloc was very apparent on the characteristics of the wastewater. At a hydraulic retention time of 4 h, the relatively short retention time was not enough to achieve any noticeable removal of ammonia without Tanfloc. In contrast, the 4 h retention time was sufficient to achieve around 70 % removal of ammonia when Tanfloc was used. This improvement in the nitrification process was attributed to the bacterial community of the biofilm as a consequence of Tanfloc use. A bacterial 16S rRNA analysis of the biofilm showed a significant increase in the percentage of ammonia-oxidizing bacteria (3.33 %) and nitrite-oxidizing bacteria (7.8 %) in the experiment using Tanfloc, compared to only 0.073 % and 0.19 % respectively, in the experiment without Tanfloc.